2016
DOI: 10.1016/j.envres.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl substance serum concentrations and immune response to FluMist vaccination among healthy adults

Abstract: Perfluoroalkyl substances (PFAS) were shown to be immunotoxic in laboratory animals. There is some epidemiological evidence that PFAS exposure is inversely associated with vaccine-induced antibody concentration. We examined immune response to vaccination with FluMist intranasal live attenuated influenza vaccine in relation to four PFAS (perfluorooctanoate, perfluorononanoate, perfluorooctane sulfonate, perfluorohexane sulfonate) serum concentrations among 78 healthy adults vaccinated during the 2010 – 2011 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
7
33
0
1
Order By: Relevance
“…Observed associations between PFAS exposure and methylation of genes involved in immune response and inflammation are consistent with the results of some previous epidemiological studies reporting altered immune system-related outcomes in adults and children exposed to PFAS (Chang et al 2016;Rappazzo et al 2017). Previous studies have generally focused on one or more of the following outcomes: allergy and atopic disease (Goudarzi et al 2016;Stein et al 2016b;Timmermann et al 2017), reduced antibody response to vaccination (Grandjean et al 2017;Looker et al 2014;Stein et al 2016a), frequency of infectious disease in children (Dalsager et al 2016;Goudarzi et al 2017;Impinen et al 2018), and inflammatory or autoimmune disease (Steenland et al 2013(Steenland et al , 2018Webster et al 2014Webster et al , 2016. Evidence from animal studies also indicates that PFOA is immunotoxic, and dietary exposure has resulted in a variety of immune system effects, including reduced weight of lymphoid organs and impaired antibody responses (DeWitt et al 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Observed associations between PFAS exposure and methylation of genes involved in immune response and inflammation are consistent with the results of some previous epidemiological studies reporting altered immune system-related outcomes in adults and children exposed to PFAS (Chang et al 2016;Rappazzo et al 2017). Previous studies have generally focused on one or more of the following outcomes: allergy and atopic disease (Goudarzi et al 2016;Stein et al 2016b;Timmermann et al 2017), reduced antibody response to vaccination (Grandjean et al 2017;Looker et al 2014;Stein et al 2016a), frequency of infectious disease in children (Dalsager et al 2016;Goudarzi et al 2017;Impinen et al 2018), and inflammatory or autoimmune disease (Steenland et al 2013(Steenland et al , 2018Webster et al 2014Webster et al , 2016. Evidence from animal studies also indicates that PFOA is immunotoxic, and dietary exposure has resulted in a variety of immune system effects, including reduced weight of lymphoid organs and impaired antibody responses (DeWitt et al 2009).…”
Section: Discussionsupporting
confidence: 88%
“…2017 ; Looker et al. 2014 ; Stein et al. 2016a ), frequency of infectious disease in children ( Dalsager et al.…”
Section: Discussionmentioning
confidence: 99%
“…This effect size is larger than later studies and can be attributed to different exposure levels, different vaccine strains, and different times elapsed since vaccination (peak antibodies vs residual antibodies). Other studies have not examined tetanus and diphtheria, but similar associations have been found in PFAS exposure and other childhood vaccinations such as rubella and mumps, 125, 126 and adult influenza vaccination such as FluMist 127 and anti-H3N2. 128…”
Section: Health Effects Associated With Exposure To Pfassmentioning
confidence: 54%
“…Results from six vaccination response studies in children and adults have been reported to date (Grandjean et al., ; Granum et al., ; Looker et al., ; Kielsen et al., 2016; Stein et al., 2016b; Abraham et al., ). Three of these studies show, for several PFASs, relatively strong inverse associations with antibody response following booster vaccination to tetanus and diphtheria in both children (Abraham et al., ; Grandjean et al., ) and adults (Kielsen et al., 2016).…”
Section: Assessmentmentioning
confidence: 99%